Characterization of an ablative fractional CO2 laser‐induced wound‐healing model based on in vitro 3D reconstructed skin. (22nd January 2023) - He, Chunyan; Zhang, Wei; Tu, Yidong; Zhong, Lingyan; Wang, Ranran; Teng, Yao; Liao, I‐Chien; Ding, Chunmei
Abstract: Objective: This study describes the development and characterization of a novel in vitro wound‐healing model based on a full‐thickness reconstructed skin by exposing the tissue to fractional ablative laser treatment. Method: A 3D full‐thickness skin model was fabricated and treated with fractional ablative CO2 laser. Wound‐healing process was characterized by HE staining, noninvasive OCT imaging, immunostaining, as well as transepidermal water loss measurement. Cytokines and proteins involved in the inflammatory and dermal remodeling process were studied by ELISA and protein array assays. Results: Fractional ablative CO2 treatment induced a wound zone of 9 mm in diameter, containing 56 micro‐wounds with 200 μm diameter and 500–700 μm in depth on reconstructed full‐thickness skin model. HE staining revealed a typical wound morphology and healing process with migration of keratinocytes, formation and extrusion of necrotic tissue, and cell inclusion in dermis, which correlates with clinical observations. Based on OCT and TEWL measurements, the re‐epithelialization took place over 2 days. Laser‐triggered keratinocytes proliferation and differentiation were demonstrated by activated Ki67 and Filaggrin expression respectively. Injury‐invoked cytokine ICAM‐1 showed instant upregulation on Day 1. Decreased epidermis thickness and depression of IGFBP‐2 protein level synergistically indicated the unavoidable thermal side effects from laser treatment. Downregulated DKK‐1 protein level and upregulation of α‐SMA together implicated the risk of potential fibrosis post‐laser treatment. Conclusion: This in vitro laser wounded reconstructed skin model captured the key events of wound‐healing process, could be used to investigate the mechanisms of wound‐healing triggered by a commonly used beauty procedure, and also provides a valuable tool for evaluating the efficacy of novel actives for the post‐procedure application.